1970
DOI: 10.3181/00379727-133-34512
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 7,12-Dimethylbenz[ ] anthracene and Splenectomy on Virus Titer and Blood Picture in Friend Virus Leukemia

Abstract: An inhibitory effect on Friend virus (FV) and Rauscher virus leukemia by the carcinogenic plycyclic aromatic hydrocarbons 7, 12-dimethylbenz [ a ] anthracene (DMlBA) and 3-methylcholanthrene was recently reported ( 1). The parameters used to show this were latent period, survival time, and spleen weight. Interference with "indirect neoplastic effects" (development of hemorrhagic necrosis and proliferation of erythroblasts in the spleen) was considered to play a greater role than interference with a "direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1971
1971
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…The increased phagocytic index K was approximately the same in DMBA-treated and untreated FV-infected mice, indicating that the nonleukemic organs, e.g., bone marrow and lymph nodes, are not influenced by the chemical. However, DMBA increased both the corrected phagocytic index a and the serum hemolysin titer in FV-infected animals in accordance with its inhibitory effect on the neoplastic transformation of the spleen as described previously (6,7).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The increased phagocytic index K was approximately the same in DMBA-treated and untreated FV-infected mice, indicating that the nonleukemic organs, e.g., bone marrow and lymph nodes, are not influenced by the chemical. However, DMBA increased both the corrected phagocytic index a and the serum hemolysin titer in FV-infected animals in accordance with its inhibitory effect on the neoplastic transformation of the spleen as described previously (6,7).…”
Section: Discussionsupporting
confidence: 87%
“…Virus. The strain of Friend virus was the same one as that used in the previous experiments (6,7). The titer of the virus pool, a 20% homogenate of leukemic spleens in sucrose stabilizer, was 104.°11D3/ml.…”
Section: Methodsmentioning
confidence: 99%
“…The depressive effect of carcinogenic polycyclic aromatic hydrocarbons (CPAH) on transformation by a DNA virus in vitro, as described in this study, may operate in a manner analogous to the previously observed phenomenon (1,2 ) of delay in malignant transformation in vivo by such carcinogens in the RNA virus-induced leukemias of Friend and Rauscher, Among the agents having an effect on viruses, interferon has attracted the greatest attention. Its influence on productive infection by many DNA and RNA viruses is well known, but its effect on transformation by some oncogenic viruses has also been reported.…”
mentioning
confidence: 76%
“…
The demonstration of an inhibitory effect of 7,12-dimethylbenz[a] anthracene (DMBA) and 3-methylcholanthrene (3-MC) on Friend and Rauscher virus leukemias (1)(2)(3)(4) led to investigation of the effect of these carcinogens on other virus-induced neoplasms. Because of the difficulty in measuring objectively the inhibition of solid neoplasms in vivo, the results of the present study were based on the effect of the two carcinogens on the in vitro transformation of 3T3 cells by SV 40 virus.

Materials and Methods.

…”
mentioning
confidence: 99%
“…The carbon clearance test was performed with the modified method described by Elliott & Schloss (). Indian ink (carbon particle suspension) was diluted 1 : 4 with 5% glucose and stirred for 20 min.…”
Section: Methodsmentioning
confidence: 99%